Dysfunction of the stress response in individuals with persistent post-concussion symptoms: a scoping review. (3rd September 2022) - Farrell, Gerard; Wang, Sizhong; Chapple, Cathy; Kennedy, Ewan; Gisselman, Angela Spontelli; Sampath, Kesava; Cook, Chad; Tumilty, Steve
Abstract: Background: Preliminary evidence suggests that individuals with persistent post-concussion symptoms (PPCS) have a dysfunctional stress response, consisting of the autonomic nervous system (ANS) and hypothalamic pituitary adrenal-axis (HPA-axis). Objectives: This review aims to explore the extent of evidence for dysfunction of the stress response in individuals with PPCS by individually mapping the literature surrounding quantifiable changes of the (1) ANS and (2) HPA-axis using non-invasive and clinical tools, and highlighting any (3) knowledge gaps. Methods: Nine electronic databases and grey literature were searched on the 1 st of June 2021 and 4 th of October 2021. Studies were included if their population was classified with PPCS, and their study stated at least one quantifiable marker of the ANS or HPA-axis using non-invasive and clinical tools. Relevant studies were screened, and data extracted. Results: A total of 37 articles were included in this scoping review. The majority of studies assessed quantifiable markers of the ANS ( n = 34), in comparison to the HPA-axis ( n = 2), and ANS and HPA-axis ( n = 1). The most common quantifiable markers of the ANS included heart rate ( n = 20), blood pressure ( n = 16), and heart rate variability ( n = 10). Cortisol was the only included quantifiable marker of the HPA-axis ( n = 2). Conclusions: Most of the evidence in this review supports quantifiable dysfunction of the ANS in those with PPCS. Further research is required investigating quantifiable dysfunction of the HPA-axis, and subsequently ANS and HPA-axis in unison, in those with PPCS.